Can guided decomposition help end-users write larger block-based programs? a mobile robot experiment - Ritschel, Nico; Fronchetti, Felipe; Holmes, Reid; Garcia, Ronald; Shepherd, David C. (Proceedings of ACM on programming languages, 2022)
Block-based programming environments, already popular in computer science education, have been successfully used to make programming accessible to end-users in domains like robotics, mobile apps, and even DevOps. Most studies of these applications have examined small programs that fit within a single screen, yet real-world programs often grow large, and editing these large block-based programs quickly becomes unwieldy. Traditional programming language features, like functions, allow programmers to decompose their programs. Unfortunately, both previous work, and our own findings, suggest that end-users rarely use these features, resulting in large monolithic code blocks that are hard to understand. In this work, we introduce a block-based system that provides users with a hierarchical, domain-specific program structure and requires them to decompose their programs accordingly. Through a user study with 92 users, we compared this approach, which we call guided program decomposition, to a traditional system that supports functions, but does not require decomposition. We found that while almost all users could successfully complete smaller tasks, those who decomposed their programs were significantly more successful as the tasks grew larger. As expected, most users without guided decomposition did not decompose their programs, resulting in poor performance on larger problems. In comparison, users of guided decomposition performed significantly better on the same tasks. Though this study investigated only a limited selection of tasks in one specific domain, it suggests that guided decomposition can benefit end-user programmers. While no single decomposition strategy fits all domains, we believe that similar domain-specific sub-hierarchies could be found for other application areas, increasing the scale of code end-users can create and understand.